Recent Progress in Infrared Thermal Imaging Nondestructive Testing Technology - WEI Jia cheng; LIU Jun yan; HE Lin; WANG Yang; HE Yu (Journal of Harbin University of Science and Technology)
Infrared thermography is a new type of digital non destructive testing technology which has developed rapidly in recent years, because it has the advantages like convenient, efficient, intuitive, large detection area and long distance non contact detection, which is widely used in aerospace, military, battery, power, electronics, architecture, medical treatment, cultural relics protection and many other fields. This paper mainly introduces and compares the characteristics and research status of several main thermal excitation methods in infrared thermography, such as halogen lamp, ultrasound, laser, pulsed light, etc. At the same time, it also introduces the research status of Thermal signal reconstruction (TSR), Lock in thermography (LT), Pulse phase infrared thermography (PPT), Principal component analysis (PCA), Dynamic thermal thermography (DTT) and Likeness optical flow (LOF) in infrared image sequence processing technology. Finally, the future development trend of infrared thermography is prospected.